Master’s Degree Environment as a Space for Personal Professional Development of Students and Professors - S. I. Pozdeeva (Высшее образование в России)
The article considers the characteristics of master’s degree studies in education as a separate stage of University education which distinguish them from bachelor’s programs. It also presents the results of a poll conducted among master’s students, which make it possible to draw a portrait of a student, find out his motivation for learning, his expectations, impressions, difficulties, and the effects of the first months of training. An average age of students is 34 years, most of them work as teachers. They are pedagogues-practitioners with different records of work. But there is a large category of students who don’t have a Bachelor’s degree in education. The survey shows that this group experiences perceptible difficulties and needs individual programs and formats of learning. The group of teachers with long records of work experiences more difficulties than the young ones as they have already lost their learning skills to a large extent. The students have marked out the educational effects of the first months of training such as reflexivity, a kind of uncertainty, mismatch, mistiming. This is caused by a fact that the ordinary state is being replaced with the situation of cognitivedissonance, reflective trap which becomes a high-power impulse for further self-development. The paper also discusses the methods of active learning and views the models of organization of collaborative activities between teacher and students and substantiates the need to replace the authoritarian model of interaction between professor and master’s degree students with the one based on communication, cooperation and designing. This model implies the dual position of a teacher – as an organizer and a participant of communication. The most suitable technology to realize studentcentered learning is problem-based learning.